1994
DOI: 10.1056/nejm199405123301902
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Aortic Dilatation and the Benefit of Long-Term β-Adrenergic Blockade in Marfan's Syndrome

Abstract: Prophylactic beta-adrenergic blockade is effective in slowing the rate of aortic dilatation and reducing the development of aortic complications in some patients with Marfan's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
509
0
42

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,004 publications
(567 citation statements)
references
References 35 publications
9
509
0
42
Order By: Relevance
“…Beta adrenergic-blocking drugs should be administered to all patients with Marfan syndrome and aortic aneurysm to reduce the rate of aortic dilatation unless contraindicated. 101 (Level of Evidence: B)…”
Section: Recommendations For Blood Pressure Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta adrenergic-blocking drugs should be administered to all patients with Marfan syndrome and aortic aneurysm to reduce the rate of aortic dilatation unless contraindicated. 101 (Level of Evidence: B)…”
Section: Recommendations For Blood Pressure Controlmentioning
confidence: 99%
“…For patients with thoracic aortic aneurysm, it is reasonable to reduce blood pressure with beta blockers and angiotensin-converting enzyme inhibitors 103 or angiotensin receptor blockers 104,105 to the lowest point patients can tolerate without adverse effects. [100][101][102] (Level of Evidence: B) 2. An angiotensin receptor blocker (losartan) is reason able for patients with Marfan syndrome, to reduce the rate of aortic dilatation unless contraindicated.…”
Section: Class Iiamentioning
confidence: 99%
“…Previous studies have shown the efficacy of β-blockers in retarding the rate of aortic dilatation, decreasing adverse end points (aortic dissection, chronic heart failure), and decreasing mortality. 80,81 Although these studies specifically evaluated patients with Marfan syndrome, logic would argue that aggressive hypertension management would be beneficial to all patients with TAA to reduce dP/dt and systemic arterial blood pressure. In addition, because TAA is closely linked to atherosclerotic disease, outpatient medical management must also include aggressive lipid management with a goal low-density lipoprotein cholesterol level of less than 70 mg/dL (to convert to mmol/L, multiply by 0.0259).…”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…The complication of Stanford type B dissection can also develop before and during delivery, however, it rare for this to develop after delivery (3,4,6,12 (11,16,17). Controversy exists regarding the teratogenic effects of β-blockers in the peripartum period.…”
Section: F I G U R E 4 A) Mu L T I P L a N A R R E F O R Ma T T E Dmentioning
confidence: 99%
“…Controversy exists regarding the teratogenic effects of β-blockers in the peripartum period. Some studies show that β-blockers are not teratogenic (18), and others mention that even long-term treatment with β-blockers is safe (16,19). According to these reports, the use of β-blockers is recommended during pregnancy in Marfan's syndrome (10,11,17,20).…”
Section: F I G U R E 4 A) Mu L T I P L a N A R R E F O R Ma T T E Dmentioning
confidence: 99%